2013
DOI: 10.1177/0894439313489656
|View full text |Cite
|
Sign up to set email alerts
|

All Political Participation Is Socially Networked?

Abstract: This research examined the influence of attention to specific forms of traditional and online media on young adults’ online and offline political participation as well as voter turnout during the fall 2012 presidential campaign. A three-wave panel survey demonstrated that attention to traditional media did not increase offline and online political participation in September; instead, participation was heightened by attention to online sources, particularly presidential candidate websites, Facebook, Twitter, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 36 publications
4
66
1
12
Order By: Relevance
“…It also confirms the results of previous studies (TOWNER, 2013: vITAK, 2011, demonstrating that interactions promoted in digital social media platforms influenced political-electoral participation of electors offline and online.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…It also confirms the results of previous studies (TOWNER, 2013: vITAK, 2011, demonstrating that interactions promoted in digital social media platforms influenced political-electoral participation of electors offline and online.…”
Section: Introductionsupporting
confidence: 80%
“…Some scholars argue that the use of such platforms promotes increased political offline participation (BODY, 2008;TOWNER, 2013;DUlIO, 2011;vITAK et al, 2011). Others advocate no links to it (BAUMGARTNER; MORRIS, 2010;ZHANG et al, 2010).…”
Section: Concept Of Participationmentioning
confidence: 99%
“…Studies have suggested that youth are now using Facebook to seek for political information, mobilize like minds, create user-generated content and share political views [15][16]. Increasingly, Facebook has been used to mobilize individuals to participate in politics and protest around the world.…”
Section: Facebook Usagementioning
confidence: 99%
“…Así se ha destacado el potencial que estas herramientas poseen para permitir incluir en la esfera pública a voces alternativas y disminuir la atención prestada por los medios a la elite política tradicional (Hong, 2013). En este sentido los medios digitales pueden, al menos idealmente, fomentar la participación política entre sus usuarios (Towner, 2013),funcionar como vehículo de difusión de visiones alternativas a las ofrecidas por los grandes medios convencionales (Gleason, 2013), como plataforma para la expresión de minorías tradicionalmente marginadas en los medios tradicionales (Bekafigo y McBride, 2013) o como canal de información sobre temas y cuestiones que las autoridades prefieren censurar o mantener ocultas (Tufecki y Wilson, 2012).…”
Section: Introductionunclassified